Case Report: Novel pathogenic variant in NFIX in two sisters with Malan syndrome due to germline mosaicism - Langley, Elizabeth; Farach, Laura S.; Mowrey, Kate (Frontiers in Genetics, 2022)
Malan syndrome is an autosomal dominant disorder caused by pathogenic variants in NFIX with less than 100 cases reported thus far. NFIX is important for stem cell proliferation, quiescence, and differentiation during development and its protein plays a role in replication, signal transduction, and transcription. As a result of pathogenic variants, symptoms of Malan syndrome include overgrowth, intellectual disability, speech delay, and dysmorphic features. Currently, the recurrence risk for this disorder is indicated at less than 1%, standard for de novo autosomal dominant disorders. Herein, we report an additional set of sisters with the same novel pathogenic variant in NFIX and clinical features consistent with Malan syndrome providing evidence of germline mosaicism. Considering the rarity of this condition in conjunction with three previous reports of germline mosaicism, it is worthwhile to investigate and re-evaluate the proper recurrence risk for this condition. This discovery would be paramount for family planning and genetic counseling practices in families with affected individuals.